Kinetics of Hydrogen Absorption and Desorption in Titanium - Suwarno Suwarno; V. A. Yartys (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
Titanium is reactive toward hydrogen forming metal hydride which has a potential application in      energy storage and conversion. Titanium hydride has been widely studied for hydrogen storage, thermal storage, and battery electrodes applications. A special interest is using titanium for hydrogen production in a hydrogen sorption-enhanced steam reforming of natural gas. In the present work, non-isothermal dehydrogenation kinetics of titanium hydride and kinetics of hydrogenation in gaseous flow at isothermal conditions were investigated. The hydrogen desorption was studied using temperature desorption spectroscopy (TDS) while the hydrogen absorption and desorption in gaseous flow were studied by temperature programmed desorption (TPD). The present work showed that the path of dehydrogenation of the TiH2 is d®b®a hydride phase with possible overlapping steps occurred. The fast hydrogen desorption rate observed at the TDS main peak temperature were correlated with the fast transformation of the d-TiH1.41 to b-TiH0.59. In the gaseous flow, hydrogen absorption and desorption were related to the transformation of b-TiH0.59 Û d-TiH1.41 with 2 wt.% hydrogen reversible content.